2018
DOI: 10.1111/jch.13292
|View full text |Cite
|
Sign up to set email alerts
|

Does leisure‐time physical activity attenuate or eliminate the positive association between obesity and high blood pressure?

Abstract: We examine the joint association of weight status and leisure-time physical activity on high blood pressure in a nationally representative sample of adults and older adults in Brazil. This was a national cross-sectional survey conducted in Brazil in 2013 (Brazilian Health Survey). The sample consisted of 59 402 participants (56% women, aged 18 to 100 years). Outcome was objectively assessed blood pressure. Body mass index (BMI) was objectively measured, while self-reported information on leisure-time physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Overweight and obesity are associated with several negative health outcomes even among adolescents, including cardiovascular diseases [2,18]. Several mechanisms may explain the positive association observed between BMI and metabolic risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overweight and obesity are associated with several negative health outcomes even among adolescents, including cardiovascular diseases [2,18]. Several mechanisms may explain the positive association observed between BMI and metabolic risk.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity (PA) is well established as a key determinant in the prevention and treatment of childhood obesity and early metabolic risk factors [2,4]. However, unlike in adults [5,6], the protective effect of PA in attenuating the association between weight status and metabolic risk indicators in youth is unclear. Although PA seems to have a positive influence on inflammatory markers associated with overweight and obesity during adolescence [7], little robust evidence is available in this context.…”
Section: Introductionmentioning
confidence: 99%
“…There is, nevertheless, an association between physical activity and hypertension, as that found in a cohort study from 2018, which showed a 28% chance of developing hypertension if the individual was physically inactive. 21 Likewise, the likelihood of a sedentary person suffering high BP nearly doubles. 21 However, the body of evidence on the effects of isometric resistance training (IRT) in normotensive, prehypertensive, and hypertensive individuals is growing.…”
mentioning
confidence: 99%
“…21 Likewise, the likelihood of a sedentary person suffering high BP nearly doubles. 21 However, the body of evidence on the effects of isometric resistance training (IRT) in normotensive, prehypertensive, and hypertensive individuals is growing. 2,4,9,10,13,20 Thus, a systematic review and meta-analysis that included randomized controlled trials in which IRT was performed in normal and hypertensive adults concluded that this form of training has the potential to significantly reduce BP and suggested it as a complementary treatment method.…”
mentioning
confidence: 99%
“…This effort focuses on em-phasizing a core theme of "sport for all, play for life" through encouraging population of all ages, genders, and backgrounds to participate in sports. Leisure-time physical activities may contribute to reduced rates of chronic diseases and mortality [9,14,15]. However, there is limited research about the PA patterns of participants in sports activities during leisure time or the health benefits of participation in sports for all.…”
mentioning
confidence: 99%